UPAYA MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS MATA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA FLASH CARD - Eminarni, Eminarni (Jurnal Likhitaprajna, 2018)
In general, reading and writing Latin letters or Indonesian spelling as well as empirical teaching practices in formal and non-formal educational institutions, such as elementary and kindergarten, reading and writing for beginner not expressive categories are subjects that cannot be separated or have become compulsory for children to accept. The study used 2 cycles. The stages in each cycle are planning, action, observation and reflection. The results showed that (1) there was an increase in the ability to read and write students when using flashcard media. In prasiklus there are 8 students or 42% who experience an increase, in cycle I which is 12 students or 63% and in cycle II it becomes 17 students or 89% who complete. Likewise in writing skills, students experience an increase in each cycle, namely in the completeness cycle reaches 9 students or 47%. In other words, there was an increase in the first cycle of 13 students or 69%, and in the second cycle there was an increase of 17 students or 90%.Keywod: media of learning, flash card, reading and writing